2013
DOI: 10.18533/jefs.v1i01.33
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and growth nexus in Gambia

Abstract: 1. The paper focuses on agriculture and economic growth nexus in Gambia. 2. The paper utilizes extensive historical context to the agriculture policies adapted so far in Gambia. 3. The window of the study is 1966 to 2009. 4. A vector error correction technique to examine the growth-agriculture relation in the Gambia is applied. 5. Interestingly, the capital per worker is found to be a significant and relevant factor input for the economic growth, while agricultural labor per acre is irrelevant in both the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The change is too acute to reflect secular decline in the Fol of trachoma. If it is not related to transmission of urogenital Ct, it could be interpreted to reflect the impact of the door-to-door distribution of topical 1% tetracycline ointment across the country, which took place in the late 1990s 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The change is too acute to reflect secular decline in the Fol of trachoma. If it is not related to transmission of urogenital Ct, it could be interpreted to reflect the impact of the door-to-door distribution of topical 1% tetracycline ointment across the country, which took place in the late 1990s 32 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Sillah (ibid), capital per worker is significant and relevant factor input for economic growth in the Gambia. Furthermore, agriculture labor per acre was found to be irrelevant in both shortand long-run analyses (Sillah 2013).…”
Section: Literature Reviewsmentioning
confidence: 98%
“…Most recent studies indicate that this low level of human development is attributable to low agricultural productivity. In a study conducted by Sillah (2013), it was found that agriculture productivity is the most important variable for economic growth in the Gambia. According to Sillah (ibid), capital per worker is significant and relevant factor input for economic growth in the Gambia.…”
Section: Literature Reviewsmentioning
confidence: 99%